Evaluation of the running-based anaerobic sprint test as a measure of repeated sprint ability in collegiate-level soccer players - Keir, D. A.; Thériault, F.; Serresse, O. (The Journal of Strength and Conditioning Research, 2013)
Repeated sprint ability (RSA) refers to an individual's ability to perform maximal sprints of short duration in succession with little recovery between sprints. The running-based anaerobic sprint test (RAST) has been adapted from the Wingate anaerobic test (WAnT) protocol as a tool to assess RSA and anaerobic power. The purpose of this study was to evaluate the relationship between performance variables and physiological responses obtained during the RAST and the WAnT using 8 collegiate-level soccer players. Participants performed a single trial of both the WAnT and the RAST. Breath-by-breath gas exchange was monitored throughout each trial, and blood lactate (BL) measures were recorded postexercise. The oxygen uptake (VO2) profile suggested that the RAST required greater contributions from aerobic metabolism although there was no difference in VO2peak (p < 0.05). Peak BL values were also similar between the RAST and the WAnT (p < 0.05). Neither peak physiological values nor performance variables (peak and mean power) were significantly correlated between protocols. The weak association in physiological responses indicates that different combinations of metabolic contributions exist between protocols, suggesting that individual performances on each test are not related in collegiate soccer players. Further studies on these relationships with players of other competitive levels and team sport athletes are warranted.